Students' Perceptions Toward Blended Media In EFL Reading Practices - Lia Yulianti; Pupung Purnawarman (Publikasi Indonesia, 2023)
Engaging students in EFL reading lessons in a large class is always a challenge for teachers. Thus, blended learning removes barriers and expands educational opportunities. The study is conducted on the concept of blended learning, which combines paper-based text with the digital game-based response system, namely Kahoot, for EFL reading context. The purpose of this study is to investigate how students perceive blended media in EFL reading practices. The participants were 76 pupils from a vocational high school. The data were gathered through observation, questionnaire, and interview. The data were quantitatively and qualitatively analyzed. The results indicated that the majority of students had favorable attitudes toward blended media in EFL reading practices. It influences their engagement, motivation, and attitudes. Additional investigation is advised to ascertain the influence on their performance in reading skills